The Impact of Mobile Money Transfer in Somalia - Hashi, Abdinasir Ismael (Journal of Technology and Systems, 2025)
Purpose: This study aims to assess the factors influencing the intention of micro-entrepreneurs in Somalia to adopt mobile money services, using the Technology Acceptance Model (TAM) as the theoretical framework. Given Somalia’s lack of formal financial infrastructure since 1991, the research investigates how mobile money contributes to financial inclusion among micro, small, and medium-sized enterprises (MSMEs). Methodology: A quantitative research design was employed, with data collected from a sample of 140 respondents using a structured survey. The TAM was used to evaluate the influence of perceived usefulness, perceived ease of use, and behavioral intention on mobile money adoption. Data were analyzed using SPSS, and model adequacy was confirmed through statistical testing for parameter estimation. Findings: The study found that behavioral intentions, perceived usefulness, and perceived ease of use significantly influence the adoption of mobile money services among Somali MSMEs. Mobile money has a positive impact on financial inclusion, allowing businesses to engage more actively in the economic ecosystem. While the attitude toward financial inclusion shows positive trends, its direct statistical significance was found to be inconclusive. Unique Contribution to Theory, Practice, and Policy: This study extends the application of TAM in fragile-state contexts and contributes to the growing literature on technology-driven financial inclusion. It offers policy insights into the need for a robust regulatory framework to ensure the stability and security of mobile money systems. Practically, it encourages governments and financial institutions to expand mobile financial services to unbanked rural populations and urges service providers to focus on usability and functionality to drive customer adoption and retention.